"Do as I Do and Not as I Say": Exploring Price‐Oriented Maverick Buying During Supplier Selection. (29th December 2016) - Scott, Marc A.; Burke, Gerard; Szmerekovsky, Joseph
ABSTRACT: This article empirically examines the occurrence of price‐oriented maverick buying (MB) during supplier selection, in a direct purchasing process context. Drawing on agency theory, maverick buying, and total cost of ownership (TCO) literature, the statistically significant existence of price‐oriented MB is investigated and the purchasing manager (PM)‐related factors that influence such noncompliant behavior are determined. A discrete choice experiment is designed to simulate a TCO‐based supplier selection process in which an established purchasing framework agreement stipulates PMs not necessarily be price‐oriented (i.e., select suppliers primarily based on lowest price), and then models PM choice behavior in the supplier selection process (SSP), utilizing a conditional logit model (CLM) to determine PM compliance to the established purchasing framework agreement and identify if price‐oriented MB exists. Statistical tests utilizing comprehensive primary and secondary data are then conducted to determine if correlational relationships exist between PM‐related factors and PM price‐orientation. Results indicate that three PM‐related factors bear a significant correlational relationship to PM price‐orientation.